Pengaruh Kecukupan Modal, BOPO, NPL, Terhadap Profitabilitas Terkait Penerapan PSAK 71 pada Perbankan di Indonesia - Miftahul Jannah; Maslichah Maslichah; Irma Hidayati (e_Jurnal Ilmiah Riset Akuntansi, 2023)
Since the global financial crisis in 2008, a group of 20 countries (G20), investors, regulators, and prudential authorities requested an increase in standards and implementation of the Impairment Loss Reserves (CKPN) to standard setters and in response, one of the independent organizations responsible for establishing and improving international accounting standards based in London (IASB) issued Financial Reporting Standards No. 9 concerning financial instruments in 2014 which includes a new standard for CKPN and will come into force in 2018. This study aims to determine the effect of capital adequacy, BOPO, NPL related to the application of PSAK 71 to banks in Indonesia. The research objects used in this study are all banking companies listed on the IDX for the 2017-2022 period. In this period there were 114 banks, but after purposive sampling, the sample that was suitable for use (meeting the criteria) in this study was 35 banking companies listed on the IDX. The data analysis technique used is multiple linear regression analysis, normality test, t test, and F test. Capital Adequacy Ratio (CAR) and Non-Performance Loans (NPL) have no effect on Return On Assets (ROA). Operational Costs Against Operating Income (BOPO) has a negative effect on Return On Assets (ROA). CAR, BOPO, and NPL have a simultaneous effect on banking profitabilityKeywords : Capital adequacy, BOPO, NPL, and profitability